2017
DOI: 10.1126/science.aal5060
|View full text |Cite
|
Sign up to set email alerts
|

Regenerating optic pathways from the eye to the brain

Abstract: Humans are highly visual. Retinal ganglion cells (RGCs), the neurons that connect the eyes to the brain, fail to regenerate after damage, eventually leading to blindness. Here, we review research on regeneration and repair of the optic system. Intrinsic developmental growth programs can be reactivated in RGCs, neural activity can enhance RGC regeneration, and functional reformation of eye-to-brain connections is possible, even in the adult brain. Transplantation and gene therapy may serve to replace or resurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 48 publications
0
102
0
Order By: Relevance
“…This resilience makes sense in light of the adaptive nature of sensory-driven adaptive reflexes such as the PLR and optokinetic reflex (OKR). Developmental constraints such as those described here are critical for models of regeneration, which is essentially an attempt to recapitulate developmental wiring, albeit to varying degrees depending on the lesion size and location (Laha et al, 2017). The findings presented here are consistent with the re-establishment of retino-OPN and retino-AOS connectivity observed in RGCs stimulated to regenerate by combined mTOR enhancement and neural activity (Lim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This resilience makes sense in light of the adaptive nature of sensory-driven adaptive reflexes such as the PLR and optokinetic reflex (OKR). Developmental constraints such as those described here are critical for models of regeneration, which is essentially an attempt to recapitulate developmental wiring, albeit to varying degrees depending on the lesion size and location (Laha et al, 2017). The findings presented here are consistent with the re-establishment of retino-OPN and retino-AOS connectivity observed in RGCs stimulated to regenerate by combined mTOR enhancement and neural activity (Lim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, RGCs do not regenerate once they are lost; this is contrary to other classes of animals, such as fish and amphibians, where retina and optic nerve can regenerate naturally. A number of animal studies have shown that under the right circumstances, mammalian RGCs are able to regenerate their axons and connect to the proper targets within the brain, resulting in some functional recovery of eye sight . The replacement of lost RGCs and the regeneration of their axons are high priorities in glaucoma research, and our dog patients may also benefit from these efforts in the future.…”
Section: Novel Treatment Strategies For the Futurementioning
confidence: 99%
“…A number of animal studies have shown that under the right circumstances, mammalian RGCs are able to regenerate their axons and connect to the proper targets within the brain, resulting in some functional recovery of eye sight. 139,140 The replacement of lost RGCs and the regeneration of their axons are high priorities in glaucoma research, and our dog patients may also benefit from these efforts in the future. The National Eye Institute (NEI) within the National Institutes of Health (NIH) predicts that these goals are achievable within 10-15 years and has made them high priorities for research funding.…”
Section: Neuroregenerationmentioning
confidence: 99%
“…Vision loss in these patients is irreversible since humans and all mammals lack the ability to generate RGCs in adulthood (Jorstad et al, 2017). There is great interest in developing regenerative therapies to restore lost vision in these patients (Benowitz et al, 2017;Calkins et al, 2017;Crair and Mason, 2016;Laha et al, 2017;Marchetti et al, 2010;Roska and Sahel, 2018;Stern et al, 2018).…”
Section: Introductionmentioning
confidence: 99%